Residents' Perception on the Authenticity of Christmas Markets in Transylvania: The Case of Cluj-Napoca - Bianca-Sorina POP-RĂCĂŞAN; István Oliver EGRESI; Diana-Elena ALEXANDRU; Cristina BOLOG; Ştefan DEZSI; Gabriela ILIEŞ; Marin ILIEŞ; Marius George OPREA (Journal of Urban and Regional Analysis)
Local events associated with religious holidays or holiday seasons provide a suitable context for the analysis of authenticity. In such regards, we conducted a survey among the visitors of the Christmas market held in ClujNapoca, Romania. The aim was to certify the authenticity of the elements of a local event as perceived by the visitors representing the local urban community. The analysis examined responses from 585 participants, exploring both qualitative and quantitative aspects. We identified seven key elements of authenticity defining the Christmas market. The study found no statistically significant differences in the perception of authenticity according to the demographic profile of the respondents.The overall opinion of the participants was that local traditional elements should predominate in an authentic Christmas market.This study could represent a ready-made tool for the decision-makers and event organisers, who should consider a participatory approach when engaging in the organisation of such events, ensuring the active involvement of the local community from the design to the implementation stage.